Analysis of deforestation around a settlement in the region of Aripuanã – MT (Research, Society and Development, 2021)
The implementation of a settlement can lead to changes in land use and coverage, generating a series of social, economic and environmental impacts. Understanding these processes can allow for better planning of public policies in order to monitor and map areas that are more susceptible to environmental problems. To date, there is no record of technical monitoring and a routine for evaluating the results of the implemented agrarian reform settlement projects. This work aimed to analyze the area around 30 km of the Medalha Milagrosa Settlement, located in the north of Mato Grosso, in order to verify if the changes in the region are due to the creation of the Settlement. Shapefille files from 2000 to 2015 made available by the PRODES project were analyzed. The results showed that between 2000 and 2005 were the years in which the deforestation rate was highest. The period in which the numbers show an increase was after the creation of the settlement in 2008 and in the following periods until 2015 the numbers showed a slight change, but always to a lesser extent. The data show that not only the activities linked to the creation of a settlement, but also the other various irregular activities that take place outside the settled area can contribute to the increase in deforestation. Thus, it is essential that both the settlements and the other properties comply with environmental laws, thus being able to guarantee a future in harmony with sustainable agrarian development, aiming at protecting the environment.